Attitudes toward organizational change and their association with exhaustion in a sample of Italian police workers - Colombo, Lara; Acquadro Maran, Daniela; Grandi, Annalisa (Frontiers in Psychology, 2023)
Change Management is an important topic for organizations and some personal characteristics may help or hinder coping with change. The aim of the present study was to find out whether attitudes toward organizational change can predict work-related exhaustion in a sample of police workers (N = 532) in northern Italy. Differences between groups in relation to role (police officers vs. other roles) and gender were also considered. The results of hierarchical regression showed that change beliefs were negatively associated to exhaustion, while resistance to change was positively related to exhaustion; role and gender were also significantly and positive associated with the dependent variable. Regarding differences between groups, police officers had lower positive change beliefs and higher levels of exhaustion compared to workers in other roles. Regarding gender, women reported higher levels of exhaustion than men. The results of the present study provide further insights into what aspects should be considered when promoting organizational change in the police work context.